A high-pressure multi-atmosphere assisted SLM gradient material preparation method and aluminum-lithium alloy coating
Through high-pressure multi-atmosphere assisted SLM technology, pulsed lasers and active gases are used to promote the reaction of carbon and nitrogen atoms with aluminum-lithium alloy melt pools under high pressure and plasma environments to form doped coatings, solving the thermal cracking problem of aluminum-lithium alloy parts prepared by SLM, and improving the hardness and mechanical properties of the material.
Patent Information
- Application Number
- CN202311794170.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-25
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-12-25
AI Technical Summary
The existing laser selection melting (SLM) technology is prone to thermal cracking problems when preparing aluminum-lithium alloy parts, resulting in reduced molding quality and mechanical properties.
The high-pressure multi-atmosphere assisted SLM method is adopted to promote the reaction of carbon and nitrogen atoms in the active gas with the molten pool material by pulsed laser under high-pressure and plasma expansion shock waves, forming a carbide and nitride-doped aluminum lithium alloy coating to improve the hardness and mechanical properties of the material.
It effectively reduces the thermal cracking tendency of aluminum-lithium alloy coating, improves the hardness and wear resistance of the surface, and realizes the external hardness and inner toughness requirements of the material.
Smart Images

Figure CN117773145B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of laser selective melting and forming, and in particular to a high-pressure multi-atmosphere assisted SLM gradient material preparation method and an aluminum-lithium alloy coating. Background Art
[0002] In the field of aerospace, the third-generation new aluminum-lithium alloy has been widely used in aircraft skins, long girders and floor beams due to its low density, high elastic modulus, good corrosion resistance and low anisotropy. However, with the improvement of the application technology of aluminum-lithium alloy, its application occasions have gradually developed towards large and complex main load-bearing structures. The manufacturing of load-bearing structures mostly adopts forming methods such as casting, forging, rolling and extrusion, and then splices them by riveting and welding. This processing method has gradually become difficult to adapt to the development needs of the complex structure and functional integration of aerospace engineering parts. In addition, in small-batch production, the preparation cost and production cycle also increase significantly. Therefore, it is urgent to develop an overall preparation technology for aluminum-lithium alloy components with low cost and short production cycle.
[0003] Additive manufacturing technology has become a research hotspot in the overall preparation technology of metal materials due to its outstanding advantages in the manufacturing of complex structural parts (integrated design and manufacturing, high processing accuracy, short manufacturing cycle, excellent physical and chemical properties of products, etc.). At present, the main additive manufacturing technologies for metal materials are laser, electron beam and arc additive manufacturing. Among them, electron beam and arc additive manufacturing technologies are very likely to cause serious heat accumulation in parts. Excessive heat input leads to coarse metal structure and increased brittle phases, which directly affects the metallurgical bonding strength, stacking dimensional accuracy and surface quality of parts. Therefore, laser additive manufacturing technology, with its characteristics of both precise forming and high-performance forming, has become the most reliable and feasible method for metal additive manufacturing.
[0004] Selective Laser Melting (SLM) can realize low-cost and short-process manufacturing of complex components by preparing parts by layer-by-layer powder laying and selectively heating different areas with laser beams. Parts formed by SLM technology usually have low surface roughness, high dimensional accuracy, and can meet the requirements of smoothness without subsequent treatment or simple surface processing. However, compared with aluminum alloys with similar composition, the addition of Li element further increases the thermal expansion coefficient and molten pool solidification temperature range of aluminum-lithium alloys, and significantly increases the intergranular low-melting eutectics, resulting in significantly higher thermal crack sensitivity of aluminum-lithium alloys than conventional aluminum alloys. Under the action of high-energy laser beams, its thermal cracking tendency is further increased, resulting in a significant decrease in the forming quality and mechanical properties of aluminum-lithium alloy parts prepared by SLM.
[0005] In order to reduce the tendency of hot cracking, some scholars have tried to use low speed, high energy density, preheating, short line scanning, increased support and other process methods or trace element alloying methods. Studies have found that it is difficult to completely avoid crack defects by simply relying on process adjustments. Although the alloying method is more effective, it can promote the transformation of coating grain types to equiaxed grains, reduce the solidification temperature range of the molten pool, and effectively refine the grain structure, but the distribution and solubility of the added trace elements in the coating are difficult to control, and the trace element particles are very easy to cluster and segregate at the grain boundaries, thereby affecting the internal stress distribution and mechanical properties of the material. The current existing processes are difficult to simultaneously meet the forming and performance requirements of SLM formed specimens, affecting the development and application of aluminum-lithium alloy additive manufacturing components in actual production. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a high-pressure multi-atmosphere assisted SLM gradient material preparation method and aluminum-lithium alloy coating. On the basis of the existing SLM forming aluminum-lithium alloy coating process, a pulsed laser is selected as a laser heat source to melt the powder and the substrate. In the preparation process of the first gradient aluminum-lithium alloy coating, CO2 in the active gas is rapidly dissociated and forms plasma under the action of laser irradiation. With the continuous absorption of laser energy, the plasma continuously decomposes active carbon atoms. Under high pressure and the expansion shock wave of the plasma, the carbon atoms fully react with the molten material inside the molten pool to form carbides, thereby realizing the carbide doping of the aluminum-lithium alloy coating, increasing the carbon content in the coating, and effectively improving the hardness and wear resistance of the surface of the first gradient aluminum-lithium alloy coating. In the process of using N2 doped active gas to prepare the third gradient aluminum-lithium alloy coating, the laser irradiates the aluminum-lithium alloy powder to form a high-temperature liquid micro-molten pool, and N2 decomposes near the high-temperature molten pool, and then penetrates into the molten pool through the gas-liquid interface and migrates and dissolves, realizing the doping of nitrides in the coating, greatly improving the hardness and mechanical properties of the third gradient aluminum-lithium alloy coating. The second gradient aluminum-lithium alloy coating is prepared using a carbon- and nitrogen-containing active atmosphere. The second gradient aluminum-lithium alloy coating is a transition layer. The two reinforcing particles in the transition coating are doped while ensuring that the alloy structure changes in a gradient and continuous transition, effectively slowing down the sudden change of the coating microstructure, reducing the accumulation of internal residual stress and thermal stress, and effectively strengthening the interlayer bonding force of the aluminum-lithium alloy gradient material. In the multi-atmosphere assisted SLM forming process, since the powder laid by the porous powder sprayer is uniform and loose, the contact area between the aluminum-lithium alloy powder and the active gas is increased. Part of the active gas stored in the gap between the powders directly dissociates into active atoms in the molten pool under the action of the high-temperature laser, which effectively promotes the in-situ synthesis reaction in the molten pool, increases the carbon content and nitrogen content in the gradient material, and further improves the mechanical properties of the material. In addition, the high-pressure environment can reduce the critical nucleation free energy of the aluminum-lithium alloy, increase the critical nucleation density and thus improve the nucleation rate, refine the grain structure and inhibit the cracking tendency of the coating. In addition, it can also effectively reduce the asymmetric degree of force on the surface molecules of the high-temperature melt, increase the reaction efficiency of the active gas molecules and the molten material, improve the flatness of the formed surface, and promote the in-situ synthesis and doping of carbides and nitrides in the coating. At the same time, as the pressure gradient decreases during the SLM forming process, the grain size inside the coating shows an increasing evolution trend, especially during the preparation of the first gradient aluminum-lithium alloy coating, the pressure is the largest, the coating grain size is significantly reduced, and the proportion of high-angle grain boundaries increases accordingly. The expansion of microcracks inside the coating requires more energy, and the strength and toughness of the first gradient aluminum-lithium alloy coating are effectively improved. Combined with the transition layer with extremely high hardness due to the doping of nitride hard phase particles and the third gradient coating, the prepared aluminum-lithium alloy gradient material presents the characteristics of hard outside and tough inside.Therefore, the present invention prepares SLM aluminum-lithium alloy gradient materials through gradient high-pressure environment and doping with various active atmospheres containing carbon and nitrogen, thereby improving the surface forming quality of the aluminum-lithium alloy material and achieving the overall performance requirements of the material being hard on the outside and tough on the inside.
[0007] The present invention achieves the above technical objectives through the following technical means.
[0008] A high-pressure multi-atmosphere assisted SLM gradient material preparation method comprises the following steps:
[0009] A first mixed gas is continuously injected into a closed working box to maintain a high-pressure environment in the working box; the first mixed gas is a mixed gas of an inert gas and a carbon-containing active gas; a micro-melting pool is formed by laser irradiation of aluminum-lithium alloy powder laid on the surface of the substrate, and the molten material in the micro-melting pool reacts with the carbon-containing active gas to form a carbide-doped first gradient aluminum-lithium alloy coating;
[0010] Expelling the first mixed gas in the sealed working box; continuously injecting the second mixed gas into the sealed working box to maintain a high-pressure environment in the working box; the second mixed gas is a mixed gas of an inert gas and a carbon-nitrogen-containing active gas; irradiating the aluminum-lithium alloy powder laid on the surface of the first gradient aluminum-lithium alloy coating with a laser to form a micro-melting pool, so that the molten material in the micro-melting pool reacts with the carbon-nitrogen-containing active gas to form a carbonitride-doped second gradient aluminum-lithium alloy coating;
[0011] Expel the second mixed gas in the closed working box; continuously inject the third mixed gas into the closed working box to maintain a high-pressure environment in the working box; the third mixed gas is a mixed gas of an inert gas and a nitrogen-containing active gas; the aluminum-lithium alloy powder laid on the surface of the second gradient aluminum-lithium alloy coating is irradiated by laser to form a micro-molten pool, and the molten material in the micro-molten pool reacts with the nitrogen-containing active gas to form a nitride-doped third gradient aluminum-lithium alloy coating.
[0012] Furthermore, the carbon-containing active gas in the first mixed gas is CO2 gas, and the volume of the CO2 gas in the first mixed gas accounts for 10% to 20%; the carbon-nitrogen active gas in the second mixed gas is CO2 gas and N2 gas, and the volume of the CO2 gas in the second mixed gas accounts for 10% to 20%; the volume of the N2 gas in the second mixed gas accounts for 20% to 30%; the nitrogen-containing active gas in the third mixed gas is N2 gas, and the volume of the N2 gas in the third mixed gas accounts for 20% to 30%.
[0013] Furthermore, the pressure of the high-pressure environment generated by the first mixed gas is P1, the pressure of the high-pressure environment generated by the second mixed gas is P2, and the pressure of the high-pressure environment generated by the third mixed gas is P3, and P1>P2>P3.
[0014] Furthermore, the pressure P1 of the high-pressure environment generated by the first mixed gas is 3.5-5.0 MPa; the pressure P2 of the high-pressure environment generated by the second mixed gas is 2.0-2.5 MPa; and the pressure P3 of the high-pressure environment generated by the third mixed gas is 1.0-1.5 MPa.
[0015] Furthermore, the active gas is maintained at a flow rate of 20 L / min to 50 L / min during the SLM forming process, so as to keep the concentration of the active gas within a set range during the reaction of the molten material.
[0016] Furthermore, a porous powder sprayer is used to spread uniform and loose aluminum-lithium alloy powder so that part of the active gas is stored inside the powder.
[0017] Furthermore, the thickness of the first gradient aluminum-lithium alloy coating and the third gradient aluminum-lithium alloy coating are both 0.8-1.0 mm, and the thickness of the second gradient aluminum-lithium alloy coating is 0.6-0.8 mm.
[0018] Furthermore, the surface of the substrate is treated to increase the surface roughness so as to improve the bonding strength between the formed aluminum-lithium alloy coating and the substrate; the treated surface is ultrasonically cleaned and dried using anhydrous ethanol.
[0019] Furthermore, the laser energy is a pulsed laser, and the parameters of the pulsed laser beam are: wavelength 1075nm, pulse energy 1J~30J, pulse period 80ms, pulse duration 20~60ms, duty cycle 50%, spot diameter ≤50μm; laser power is 80~100W, laser beam scanning speed is 100mm / s, and scanning spacing is 100~120μm.
[0020] An aluminum-lithium alloy coating is formed on the surface of a substrate using the high-pressure multi-atmosphere assisted SLM gradient material preparation method.
[0021] The beneficial effects of the present invention are:
[0022] 1. The high-pressure multi-atmosphere assisted SLM gradient material preparation method described in the present invention uses pulsed laser as the irradiation heat source. Compared with the traditional continuous laser mode, the pulsed laser can accurately adjust the distribution of laser energy in the time domain by adjusting the pulse parameters, thereby directly affecting the microstructure of the formed part. In the SLM forming preparation process, the pulsed laser allows the molten pool to cool and solidify periodically, thereby enhancing the stirring effect on the liquid molten pool. The stirring effect not only reduces the dendrite spacing and makes the molten pool elements more evenly and fully diffused, but also increases the recrystallization ratio of the molten pool and reduces the anisotropy of the grains; in addition, the matrix temperature is reduced under the action of the pulsed laser, and the cooling rate of the molten pool is increased, so the heat accumulation of the overall aluminum-lithium alloy material is less, and the residual stress of the material is significantly reduced.
[0023] 2. In the high-pressure multi-atmosphere assisted SLM gradient material preparation method described in the present invention, the first mixed gas includes Ar and 10% to 20% CO2 active gas by volume, and Ar and 10% to 20% CO2 active gas by volume are used as the atmosphere doping in the first gradient aluminum-lithium alloy coating preparation process. Under the action of high-power density intense pulse laser irradiation, the CO2 in the active gas dissociates under high temperature and high pressure environment and forms plasma above the molten pool. In the plasma, CO2 dissociates into CO and O, and continues to absorb laser energy to further decompose into C and O. Since the solubility of active carbon atoms in high-temperature liquid metal is significantly higher than that of oxygen atoms, under the high-pressure auxiliary environment and the expansion shock wave of the plasma itself, the active carbon atoms in the dissociated material are stirred and modulated with the molten material inside the molten pool to form carbide particles in situ and evenly dispersed in the coating. The carbon content near the surface of the aluminum-lithium alloy coating increases, effectively improving the hardness and wear resistance of the first gradient aluminum-lithium alloy coating; at the same time, CO2 as a high thermal conductivity gas can effectively increase the overall thermal conductivity of the molten alloy powder and increase the cooling rate of the molten pool, thereby further strengthening the microstructure and mechanical properties of the aluminum-lithium alloy coating.
[0024] 3. The high-pressure multi-atmosphere assisted SLM gradient material preparation method described in the present invention, the third mixed gas includes Ar and N2 active gas with a volume ratio of 20% to 30%, Ar and N2 active gas with a volume ratio of 20% to 30% are used as the atmosphere doping in the preparation process of the third gradient aluminum-lithium alloy coating, and N2 in the active gas dissociates into active nitrogen atoms under the action of high-power laser irradiation. Similarly, under the synergistic action of the high-pressure environment and the plasma expansion shock wave, the nitrogen atoms above the high-temperature molten pool penetrate into the molten pool and stir and modulate with the molten material to achieve the doping of nitrides in the third gradient coating. Since the hardness of nitride particles is significantly higher than that of carbides, the hardness and mechanical properties of the third gradient aluminum-lithium alloy coating are greatly improved compared with the first gradient aluminum-lithium alloy coating. In addition, the high-pressure environment in the working box increases the nitrogen partial pressure in the SLM melting and solidification process, and the solute nitrogen atoms in the molten pool do not reach the saturated solubility, so that the nitrogen content diffused into the high-temperature molten pool during the forming process increases, which effectively increases the nitriding amount of the coating; on the other hand, the surface pressure of the molten pool increases with the high-pressure environment, and the nitrogen escape behavior is also effectively suppressed. Therefore, the third gradient aluminum-lithium alloy coating prepared under high pressure and with the assistance of nitrogen-containing active gas has higher surface hardness and mechanical stability.
[0025] 4. The high-pressure multi-atmosphere assisted SLM gradient material preparation method described in the present invention, the third mixed gas includes Ar+(10%-20%)CO2+(20%-30%)N2 active gas, Ar+(10%-20%)CO2+(20%-30%)N2 active gas is used as the atmosphere doping in the transition coating preparation process, CO2 and N2 simultaneously dissociate into active carbon atoms and nitrogen atoms under laser irradiation, and the active atoms react with the molten material in the laser micro-melting pool, thereby achieving the simultaneous doping of carbides and nitrides in the transition coating. It should be noted that since the ionization energy of carbon (11.26eV) is lower than that of nitrogen (14.35eV), the carbon atoms in the transition layer react more easily with the molten material in the molten pool than the nitrogen, resulting in that under the assistance of the same N2 concentration atmosphere, the number of nitride inclusions in the transition layer is less than that of the third gradient aluminum-lithium alloy coating, and the overall hardness of the coating is lower than that of the third gradient aluminum-lithium alloy coating, while its brittleness is also effectively alleviated. In addition, under the action of gradient pressure, the degree of microstructure refinement inside the transition layer is between the first and third gradient aluminum-lithium alloy coatings, which effectively reduces the mutation of the material microstructure. Therefore, the existence of the transition layer makes the mechanical properties and organization of the aluminum-lithium alloy material present a continuous transition change, reduces the accumulation of thermal stress and residual stress inside the material, significantly enhances the bonding strength between the gradient coatings, and further extends the service life of the SLM gradient material.
[0026] 5. The high-pressure multi-atmosphere assisted SLM gradient material preparation method described in the present invention lays a uniform and loose aluminum-lithium alloy powder on a substrate through a porous powder sprayer. The loose powder layer structure allows part of the active gas to be stored inside the powder. Under the action of the high-temperature laser, the active atoms are directly dissociated inside the molten pool, which increases the concentration of active atoms dissolved in the molten pool, effectively promotes the reaction efficiency of the molten material and the active gas, and the carbide and nitride doping content in the gradient material is increased, and the mechanical properties of the aluminum-lithium alloy material are further improved.
[0027] 6. The high-pressure multi-atmosphere assisted SLM gradient material preparation method described in the present invention prepares SLM samples through a high-pressure assisted process. The physical effect of pressure provides nucleation work for the molten metal, prompting more atomic groups to participate in crystallization nucleation, significantly improving the nucleation rate of the molten pool, and thus achieving the effect of grain refinement. In addition, the high-pressure environment affects the surface tension between the molten metal and the gas, reduces the asymmetric degree of molecular force on the surface of the high-temperature melt, increases the carbon and nitrogen partial pressures at the gas-liquid interface on the surface of the molten pool, and increases the absorption concentration of active carbon atoms and nitrogen atoms in the molten pool. While improving the flatness of the formed surface, it also effectively promotes the in-situ synthesis doping of carbides and nitrides in the aluminum-lithium alloy coating. At the same time, the enhanced stirring effect of the pulsed laser makes these inclusion particles more evenly distributed in the coating, thereby further improving the mechanical properties of the aluminum-lithium alloy.
[0028] 7. The high-pressure multi-atmosphere assisted SLM gradient material preparation method described in the present invention uses a gradient pressure environment to assist the SLM gradient material forming, so that the grain size of the material shows an increasing evolution trend from the inside to the outside, wherein the grain size of the first gradient coating is the smallest, and the number of fine grains per unit volume is significantly greater than that of the transition layer and the third gradient layer. Therefore, when plastic deformation occurs, due to the large number of favorable grains, the deformation energy is evenly dispersed to each grain, the deformation non-uniformity of the fine-grained metal is reduced, and the internal stress distribution of the coating is more uniform. In addition, the smaller the grain, the easier it is for grain boundary sliding to occur. Due to the mobility of the grain boundary, the stress concentration generated by the dislocation near the grain boundary is easily relaxed, resulting in a relatively dispersed position of the stress concentration, which is conducive to the continued plastic deformation of the coating, and the plasticity and ductility of the first gradient coating are significantly improved. The grain refinement effect of the transition layer and the third gradient coating gradually weakens as the pressure decreases during the preparation process, and the strength and toughness of the coating decreases. However, due to the doping of high-hardness nitrides, the surface hardness and wear resistance of the transition layer and the third gradient coating are greatly improved, making the prepared aluminum-lithium alloy gradient material have the performance characteristics of being hard on the outside and tough on the inside.
[0029] 8. The high-pressure multi-atmosphere assisted SLM gradient material preparation method described in the present invention, all process parameters including pulse parameters, laser parameters, high pressure and atmosphere parameters can be controlled through the algorithm, has the advantages of simple operation, low cost, high efficiency, etc., is easy to realize industrial application, and is oriented to the service environment of aviation aluminum-lithium alloys, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. The drawings described below are some embodiments of the present invention. For ordinary technicians in this field, it is obvious that other drawings can be obtained based on these drawings without paying any creative work.
[0031] Figure 1 This is a schematic diagram of the method for high-pressure multi-atmosphere assisted SLM gradient materials described in the present invention.
[0032] Figure 2 This is the cross-sectional morphology and carbon and nitrogen element contents of the gradient material prepared in Example 1 of the present invention.
[0033] Figure 3 The average microhardness of the cross section of each gradient coating layer of the sample prepared in Example 1 of the present invention.
[0034] Figure 4 This is a comparison chart of the surface microhardness of the gradient materials prepared in various embodiments of the present invention.
[0035] In the figure:
[0036] 1-working box; 2-substrate; 3-porous powder sprayer; 4-pressure pump; 5-vacuum pump; 6-gas flow meter; 7-pressure gauge. DETAILED DESCRIPTION
[0037] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0038] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "upper", "lower", "axial", "radial", "vertical", "horizontal", "inner", "outer" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0039] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0040] like Figure 1 As shown, the high-pressure multi-atmosphere assisted SLM gradient material preparation method of the present invention comprises the following steps:
[0041] Before the SLM forming operation, the working box is cleaned of impurities and powders, and the surface of the substrate 2 is roughly ground to improve the bonding strength between the formed aluminum-lithium alloy coating and the substrate 2; the treated surface is ultrasonically cleaned and dried with anhydrous ethanol;
[0042] After argon is injected into the working box 1 for a period of time, the first mixed gas is continuously injected, and the first mixed gas is a mixed gas of argon and CO2 gas; the volume of CO2 gas accounts for 10% to 20%; the gas flow meter 6 at the inlet and outlet of the working box monitors that all active gases maintain a flow rate of 20L / min to 50L / min during the SLM process; a pressure pump 4 is used to maintain the high pressure environment in the working box 1, and a pressure gauge 7 is set in the working box 1 to monitor and ensure that the pressure is in the range of 3.5 to 5.0MPa;
[0043] A loose aluminum-lithium alloy powder with a powder layer thickness of 40 to 50 μm and a diameter range of 20 to 63 μm is laid on the substrate by a porous powder sprayer; the aluminum-lithium alloy powder laid on the surface of the substrate 2 is irradiated by using appropriate pulsed laser parameters and process paths to form a micro-melting pool, so that the molten material in the micro-melting pool reacts with the carbon-containing active gas to form a carbide-doped first gradient aluminum-lithium alloy coating; in addition, the grain structure of the coating is significantly refined under the action of a relatively high pressure, thereby achieving a synergistic enhancement of the hardness and toughness of the formed first gradient aluminum-lithium alloy coating, and the aluminum-lithium alloy powder laying and irradiation operations are repeated until the thickness of the first gradient aluminum-lithium alloy coating reaches 0.8 to 1.0 mm;
[0044] After the first gradient aluminum-lithium alloy coating is completed, argon gas is injected into the working box 1 to exhaust the first mixed gas; then the second mixed gas is continuously injected into the closed working box 1, and the second mixed gas is a mixed gas of Ar gas and CO2+N2 active gas; the volume of the CO2 gas in the second mixed gas accounts for 10% to 20%; the volume of the N2 gas in the second mixed gas accounts for 20% to 30%; a pressure pump 4 is used to maintain the high-pressure environment in the working box 1, and a pressure gauge 7 is set in the working box 1 to monitor and ensure that the pressure is in the range of 2.0 to 2.5 MPa; when the pulse laser parameters and the process path remain unchanged, the aluminum-lithium alloy powder laid on the surface of the first gradient aluminum-lithium alloy coating is irradiated by laser to form a micro-molten pool, so that the molten material in the micro-molten pool reacts with the carbon-containing and nitrogen-containing active gas to form a carbonitride-doped second gradient aluminum-lithium alloy coating; the second gradient aluminum-lithium alloy coating is the transition layer, and the powder laying and irradiation operations are repeated until the thickness of the transition layer is 0.6 to 0.8 mm;
[0045] After the second gradient aluminum-lithium alloy coating is completed, argon gas is injected into the working box 1 to exhaust the second mixed gas; then the third mixed gas is continuously injected into the closed working box 1 to maintain a high-pressure environment in the working box 1; the third mixed gas is a mixed gas of Ar gas and N2 active gas; the volume of N2 gas accounts for 20% to 30%. A pressure pump 4 is used to maintain the high-pressure environment in the working box 1, and a pressure gauge 7 is set in the working box 1 to monitor and ensure that the pressure is in the range of 1.0 to 1.5 MPa; when the pulse laser parameters and process path remain unchanged, the aluminum-lithium alloy powder laid on the surface of the second gradient aluminum-lithium alloy coating is irradiated by laser to form a micro-melting pool, so that the molten material in the micro-melting pool reacts with the nitrogen-containing active gas to form a nitride-doped third gradient aluminum-lithium alloy coating. The powder laying and irradiation operations are repeated until the thickness of the third gradient aluminum-lithium alloy coating is 0.8 to 1 mm.
[0046] The high-pressure multi-atmosphere assisted SLM gradient material preparation method described in the present invention continuously injects carbon-containing and nitrogen-containing active gases into the work box 1 and maintains a gradient high-pressure environment, selects pulsed laser as a radiation heat source, and performs SLM forming preparation on the aluminum-lithium alloy powder. During the forming process, the molten material in the molten pool reacts with the carbon-containing and nitrogen-containing active gases to complete the doping of different strengthening phases. At the same time, the microstructure of the gradient coating shows a transitional evolution trend under the action of different pressures. The prepared aluminum-lithium alloy gradient material achieves the performance requirements of hard outside and tough inside.Carbon-containing active gas is used as the atmosphere doping in the SLM process of the first gradient aluminum-lithium alloy coating. Under the action of laser irradiation, active carbon atoms are dissociated and plasma is formed above the molten pool. Under the high pressure and the expansion shock wave of the plasma, the carbon atoms are stirred and modulated with the molten material in the molten pool, which greatly increases the carbon content on the surface of the aluminum-lithium alloy, thereby enhancing the wear resistance and mechanical stability of the first gradient aluminum-lithium alloy coating. Nitrogen-containing active gas is used as the atmosphere doping in the preparation process of the third gradient aluminum-lithium alloy coating. The active nitrogen atoms separated under the action of laser penetrate into the high-temperature molten pool through the gas-liquid interface and migrate and dissolve, achieving the coating. The doping of high-hardness nitride particles in the layer further improves the surface hardness and wear resistance of the third gradient aluminum-lithium alloy coating compared to the first gradient coating doped with only carbides; the second gradient aluminum-lithium alloy coating is prepared by introducing carbon- and nitrogen-containing active gases, and the active gases simultaneously dissociate carbon atoms and nitrogen atoms under laser irradiation. The active atoms react with the high-temperature molten pool to achieve the simultaneous doping of carbides and nitrides, which is beneficial to the gradient continuous transition change of the mechanical properties of the aluminum-lithium alloy gradient material and effectively enhances the interlayer bonding force of the gradient material; a porous powder sprayer is used to lay a uniform and loosely structured aluminum-lithium alloy powder, and part of the active gas penetrates into the loose Inside the loose powder layer, active atoms are directly dissociated under the action of laser irradiation and melted in the high-temperature molten pool. The carbon and nitrogen contents in the molten pool increase, and the mechanical properties of the aluminum-lithium alloy material are further improved. SLM forming preparation under high pressure is conducive to the increase of the nucleation rate in the molten pool, making the grain structure of the aluminum-lithium alloy coating more refined. The high-pressure auxiliary process also increases the absorption concentration of carbon and nitrogen atoms by the molten metal in the molten pool, promotes the in-situ synthesis and doping of carbides and nitrides in the aluminum-lithium alloy gradient material, improves the molding quality of the prepared material, and further improves the hardness and mechanical properties of the gradient material. High pressure further assists SLM forming, so that the grain size inside the material shows an increasing evolution trend as the pressure of the working environment decreases. Therefore, the grain size of the first gradient coating is the smallest, and the coating exhibits the highest strength and toughness. Combined with the transition layer doped with high-hardness nitride particles and the third gradient aluminum-lithium alloy coating, the gradient high-pressure assisted process makes the prepared SLM gradient material have the performance characteristics of hard outside and tough inside. Using pulsed laser for SLM forming preparation, the stirring effect in the molten pool is enhanced, making the element distribution more uniform and effectively increasing the cooling rate of the molten pool, reducing the heat accumulation of the material, and effectively reducing the residual stress of the prepared material.
[0047] In order to make the purpose, technical solutions and advantages of the present invention clearer, 2195 aviation aluminum-lithium alloy is selected as a research object, and the present invention is described in detail in combination with specific embodiments.
[0048] Embodiment 1:
[0049] The high-pressure multi-atmosphere assisted SLM gradient material preparation method described in Example 1 comprises the following steps:
[0050] S01: Before the SLM forming operation, the working box 1 is cleaned of impurities and powders, and the 2195 aluminum-lithium alloy substrate 2 is sanded with sandpaper of 800# and 1000# grain sizes to improve the bonding strength between the formed aluminum-lithium alloy coating and the substrate 2; then the treated surface is ultrasonically cleaned and dried with anhydrous ethanol;
[0051] S02: After injecting argon gas into the working box 1 for 15 minutes, Ar+10% CO2 active gas is introduced;
[0052] S03: The flow rate of the active gas is monitored by the gas flow meter 6 at the inlet and outlet of the working box 1. During the SLM process, all active gases maintain a flow rate of 50 L / min;
[0053] S04: Use a pressure pump 4 to maintain a high pressure environment in the working box, and set a pressure gauge 7 in the working box 1 to monitor and ensure that the pressure during the SLM process is maintained at 3.5 MPa;
[0054] S05: laying a loose aluminum-lithium alloy powder with a powder layer thickness of 50 μm and a diameter of 50 μm on the substrate 2 through a porous powder sprayer 3;
[0055] S06: IPG-YLS-5000 fiber laser was selected, and the light output mode was modulated into pulse mode. The specific processing parameters of the laser were: wavelength 1075nm, pulse energy 20J, pulse period 80ms, pulse duration 40ms, duty cycle 50%, and spot diameter 50μm. The specific process parameters of the SLM forming process were: laser power 90W, scanning speed 100mm / s, scanning spacing 110μm, and the scanning path of the forming process was an interlayer orthogonal strategy. Repeat the aluminum-lithium alloy powder laying operation until the thickness of the first gradient aluminum-lithium alloy coating reached 0.8mm;
[0056] S07: After the first gradient aluminum-lithium alloy coating is prepared, argon gas is injected into the working box for 15 minutes to exhaust the first mixed gas, and then Ar+10% CO2+20% N2 is introduced, and a high pressure environment of 2.0 MPa is maintained through a pressure gauge 7;
[0057] S08: When the pulse laser parameters and process path remain unchanged, the thickness of the second gradient aluminum-lithium alloy coating (and transition layer) prepared by repeated powder laying work is 0.6 mm;
[0058] S09: Inject argon gas for 15 minutes into the working box 1 to exhaust the second mixed gas, then introduce Ar+20% N2, and maintain a high pressure environment of 1.0 MPa through the pressure gauge 7;
[0059] S10: Under the same process conditions, the powder layer is laid multiple times and melted to finally prepare the third gradient aluminum-lithium alloy coating with a thickness of 0.8 mm. According to the above processing parameters, SLM operation is performed in a work box with gradient high pressure and multiple active atmospheres to complete the preparation of aluminum-lithium alloy gradient materials with no defects in the matrix and excellent wear resistance.
[0060] The cross-sectional morphology of the aluminum-lithium alloy prepared in Example 1 is as follows: Figure 2 As shown in the figure, compared with the traditional SLM formed specimen, the microstructure of the gradient material prepared in Example 1 shows a gradually refined evolution trend from the surface to the inside. The first gradient coating prepared under the highest pressure environment has the finest grain structure and the coating has the highest toughness. In addition, the EDS point scanning results of points A and B show that the hard phase particles in the gradient material have 12.68at.% C doping and 25.36at.% N doping, respectively, which confirms that the carbon-containing and nitrogen-containing active gases achieve the doping of carbides and nitrides in the SLM material. Figure 3 The average microhardness of each gradient coating cross section of the sample prepared in Example 1 shows that the microhardness increases from the first gradient layer to the third gradient layer. Combined with the decreasing toughness trend of the gradient material from the inside to the outside, the SLM aluminum-lithium alloy gradient material prepared in Example 1 achieves the performance requirements of hard outside and tough inside. In addition, Figure 4 As shown in the figure, under the synergistic effect of high-pressure assistance and in-situ synthesis of active gases, the carbon and nitrogen elements inside the aluminum-lithium alloy material increase, greatly improving the surface hardness of the material. The microhardness value reaches 152.5HV, which is 35.5% higher than the average hardness value of 112.7HV on the traditional SLM surface. This is of great significance for low-cost and efficient improvement of the wear resistance of SLM aluminum-lithium alloy materials.
[0061] Embodiment 2
[0062] On the basis of Example 1, the active gas Ar+
[0063] 15% CO2, the pressure is maintained at 5.0MPa; the active gas Ar+15% CO2+25% N2 used to prepare the transition layer, the pressure is maintained at 2.5MPa; the active gas Ar+25% N2 in the preparation process of the third gradient aluminum-lithium alloy coating, the pressure is maintained at 1.5MPa; the flow rate of all active gases is 35L / min.
[0064] Compared with the material prepared in Example 1, the overall microstructure of the gradient material obtained in Example 2 is more refined, and the C content and N content of the two hard phase particles doped are increased to 16.92at.% and 28.2at.%, respectively. Example 2 uses a higher pressure environment, a lower gas flow rate, and a higher proportion of CO2 and N2 doped active gases to assist SLM forming of the sample. The reaction efficiency of the molten material and the active gas is improved, the size and doping amount of carbides and nitrides in the material are increased, and the strengthening effect of the aluminum-lithium alloy material is effectively improved. Figure 4 As shown, the surface microhardness value of the aluminum-lithium alloy material prepared in this embodiment is 164.7HV, which is 46.1% higher than the average hardness value of 112.7HV of the sample surface prepared by traditional SLM, and 8% higher than the average hardness of 152.5HV of the sample surface after treatment in Example 1. Appropriately increasing the pressure, reducing the active gas flow rate and increasing the ratio of CO2 and N2 in the gas make the stirring reaction between the molten material in the molten pool and the dissociated active atoms more complete, and the hardness and mechanical stability of the surface of the aluminum-lithium alloy material are further improved.
[0065] Embodiment 3
[0066] On the basis of Example 1, the active gas Ar+20% CO2 in the preparation process of the first gradient aluminum-lithium alloy coating in Example 3 was maintained at a pressure of 5.0 MPa, and the first gradient aluminum-lithium alloy coating was prepared with a thickness of 1.0 mm; the active gas Ar+20% CO2+30% N2 used in the preparation of the transition layer was maintained at a pressure of 2.5 MPa, and the transition coating thickness was 0.8 mm; the active gas Ar+30% N2 in the preparation process of the third gradient aluminum-lithium alloy coating was maintained at a pressure of 1.5 MPa, and the final preparation thickness of the third gradient coating was 1.0 mm; all active gas flow rates were 20 L / min; and the laser power was set to 1000 W.
[0067] Due to the increase in laser power and the thickness of each layer of gradient coating, the sample processed in Example 3 is doped with more and larger carbide and nitride particles. The C content of the carbide particles is 17.18 at.%, and the N content of the nitride particles is 29.7 at.%. However, due to the accumulated heat influence inside the material, the microstructure of the sample prepared in Example 3 does not show obvious refinement effect compared with Example 1 even under increased pressure. The surface microhardness value of the aluminum-lithium alloy material prepared in this example is 160.2 HV, which is 42.1% higher than the average hardness of 112.7 HV of the traditional SLM surface. It can be seen that the material prepared in Example 3 also has high wear resistance and mechanical stability.
[0068] Table 1 shows the characterization results of samples treated with different processes of the present invention.
[0069]
[0070] An aluminum-lithium alloy coating is formed on the surface of a substrate 2 using the high-pressure multi-atmosphere assisted SLM gradient material preparation method of the present invention. The substrate 2 here can be the skin of an aircraft.
[0071] It should be understood that although this specification is described according to various embodiments, not every embodiment contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.
[0072] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high-pressure multi-atmosphere assisted SLM gradient material preparation method, characterized in that: The steps include: A first mixed gas is continuously injected into a closed working box (1) to maintain a high-pressure environment in the working box (1); the first mixed gas is a mixed gas of an inert gas and a carbon-containing active gas; a micro-molten pool is formed by laser irradiation of aluminum-lithium alloy powder laid on the surface of a substrate (2), and the molten material in the micro-molten pool reacts with the carbon-containing active gas to form a carbide-doped first gradient aluminum-lithium alloy coating; Expelling a first mixed gas from a sealed working box (1); continuously injecting a second mixed gas into the sealed working box (1) to maintain a high-pressure environment in the working box (1); the second mixed gas being a mixed gas of an inert gas and a carbon-nitrogen-containing active gas; irradiating the aluminum-lithium alloy powder laid on the surface of the first gradient aluminum-lithium alloy coating with a laser to form a micro-melting pool, so that the molten material in the micro-melting pool reacts with the carbon-nitrogen-containing active gas to form a carbonitride-doped second gradient aluminum-lithium alloy coating; Expelling the second mixed gas in the sealed working box (1); continuously injecting a third mixed gas into the sealed working box (1) to maintain a high-pressure environment in the working box (1); the third mixed gas is a mixed gas of an inert gas and a nitrogen-containing active gas; irradiating the aluminum-lithium alloy powder laid on the surface of the second gradient aluminum-lithium alloy coating with laser to form a micro-melting pool, so that the molten material in the micro-melting pool reacts with the nitrogen-containing active gas to form a nitride-doped third gradient aluminum-lithium alloy coating; The pressure P1 of the high-pressure environment generated by the first mixed gas, the pressure P2 of the high-pressure environment generated by the second mixed gas, and the pressure P3 of the high-pressure environment generated by the third mixed gas, P1>P2>P3; the pressure P1 of the high-pressure environment generated by the first mixed gas is 3.5~5.0MPa; the pressure P2 of the high-pressure environment generated by the second mixed gas is 2.0~2.5MPa; the pressure P3 of the high-pressure environment generated by the third mixed gas is 1.0~1.5MPa.
2. The high pressure multi-atmosphere assisted SLM gradient material preparation method according to claim 1, characterized in that: The carbon-containing active gas in the first mixed gas is CO2 gas, and the volume of the CO2 gas in the first mixed gas accounts for 10% to 20%; the carbon-nitrogen active gas in the second mixed gas is CO2 gas and N2 gas, and the volume of the CO2 gas in the second mixed gas accounts for 10% to 20%; the volume of the N2 gas in the second mixed gas accounts for 20% to 30%; the nitrogen-containing active gas in the third mixed gas is N2 gas, and the volume of the N2 gas in the third mixed gas accounts for 20% to 30%.
3. The high pressure multi-atmosphere assisted SLM gradient material preparation method according to claim 1, characterized in that: The active gas is maintained at a flow rate of 20 L / min to 50 L / min during the SLM forming process, so as to keep the concentration of the active gas within a set range during the reaction of the molten material.
4. The high pressure multi-atmosphere assisted SLM gradient material preparation method according to claim 1, characterized in that: The aluminum-lithium alloy powder is evenly and loosely laid by a porous powder sprayer to allow part of the active gas to be stored inside the powder.
5. The high pressure multi-atmosphere assisted SLM gradient material preparation method according to claim 3, characterized in that: The thickness of the first gradient aluminum-lithium alloy coating and the third gradient aluminum-lithium alloy coating are both 0.8-1.0 mm, and the thickness of the second gradient aluminum-lithium alloy coating is 0.6-0.8 mm.
6. The high pressure multi-atmosphere assisted SLM gradient material preparation method according to claim 1, characterized in that: The surface of the substrate (2) is treated to increase the surface roughness, so as to improve the bonding strength between the formed aluminum-lithium alloy coating and the substrate (2); and the treated surface is ultrasonically cleaned and dried using anhydrous ethanol.
7. The high pressure multi-atmosphere assisted SLM gradient material preparation method according to claim 1, characterized in that: The laser energy is pulsed laser, and the parameters of the pulsed laser beam are: wavelength 1075nm, pulse energy 1J-30J, pulse period 80ms, pulse duration 20-60ms, duty cycle 50%, spot diameter ≤50μm; laser power is 80-100W, laser beam scanning speed is 100mm / s, and scanning spacing is 100-120μm.
8. An aluminum-lithium alloy coating, characterized in that: An aluminum-lithium alloy coating is formed on the surface of a substrate (2) using the high-pressure multi-atmosphere assisted SLM gradient material preparation method described in any one of claims 1 to 7.
Citation Information
Patent Citations
Method for preparing TiCN component gradient hard coating through advanced plasma assisted arc (APA-Arc) technology
CN105154825A
Laser preparation device and method for in-situ synthesis of TiC-reinforced titanium-based composite material
CN108465814A